Corporate misconduct, trade credit and charitable donations: evidence from Chinese listed companies. Issue 3 (5th August 2019) - Liu, Zheming; Zeng, Saixing; Xu, Xiaodong; Lin, Han; Ma, Hanyang
Abstract : Purpose: The purpose of this paper is to investigate how revelations of corporate misconduct are associated with trade credit. Specifically, it investigates how this association varies in different regions, in different types of industries and in response to companies' subsequent charitable donations. Design/methodology/approach: The authors empirically tested various hypotheses using a sample of 2, 725 Chinese A-share listed companies from 2009 to 2014 based on signaling theory. Fixed effect models underpinned the methods used. Findings: The authors found that corporate misconduct has a significant negative impact on an irresponsible company's trade credit received and granted, and the negative impact is heterogeneous for different regions and industries. There is no evidence that charitable donations mitigate the effect on the trade credit of irresponsible companies following revelations of corporate misconduct. Practical implications: The results suggest that listed companies in China should obey national and local laws and regulations if they wish to avoid the risk of significant trade credit loss. If a company's violation of these laws and regulations is disclosed, making charitable donations is not an effective strategy for safeguarding trade credit. Originality/value: This study enriches understanding on the consequences of corporate misconduct and extends the literature on trade credit. It fills a research gap by identifying the impact of corporate misconduct on trade credit.